2004
DOI: 10.1016/j.jpainsymman.2004.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Course of fatigue in women receiving chemotherapy and/or radiotherapy for early stage breast cancer

Abstract: Although much has been learned about the complication of fatigue during breast cancer treatment, the possibility that there are differences across treatment modalities in breast cancer patients' experience of fatigue has not yet been established. In this study, fatigue was assessed in 134 women receiving chemotherapy and radiotherapy or radiotherapy only for early stage breast cancer. Comparisons of fatigue during initial treatment indicated that women who received chemotherapy reported greater fatigue severit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
99
1
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 143 publications
(119 citation statements)
references
References 16 publications
16
99
1
3
Order By: Relevance
“…12,13 Eligibility was determined by chart review and consultation with the attending physician. Eligible patients were recruited and informed consent was obtained during an outpatient clinic visit following their surgical procedure but before the initiation of chemotherapy (CTϩRT group) or radiotherapy (RT group).…”
Section: Methodsmentioning
confidence: 99%
“…12,13 Eligibility was determined by chart review and consultation with the attending physician. Eligible patients were recruited and informed consent was obtained during an outpatient clinic visit following their surgical procedure but before the initiation of chemotherapy (CTϩRT group) or radiotherapy (RT group).…”
Section: Methodsmentioning
confidence: 99%
“…In this longitudinal survey demographic variables and factors associated with the tumour and anti-cancer treatment were unrelated to the fatigue. A large body of evidence exists to support the finding that CRF during anti-cancer treatment is not associated with tumour stage (12,22,23,46,51,56,60,(68)(69)(70) or any demographic (12,22,23,34,49,55,56,60,62,64,(66)(67)(68)(69)(70)(71) or treatment-related variables (12,22,23,46,51,53,55,60,64,(68)(69)(70)(71)(72). In contrast, two studies have reported that females experience more fatigue then males (62,73), three have demonstrated an association between increasing age and lower fatigue (12,34,53), one between marital status and fatigue, with divorced women experiencing the most fatigue …”
Section: Fatigue During Anti-cancer Treatmentmentioning
confidence: 99%
“…However, the test-retest reliability of this scale is weak, perhaps because of the relatively long recall period. The FSI has mainly been used in studies examining the effect of chemotherapy for breast cancer [51][52][53][54][55][56]. These studies have shown that the majority of patients with breast cancer who receive chemotherapy are likely to experience some degree of CRF.…”
Section: Multidimensional Toolsmentioning
confidence: 99%